Utilisasi pelayanan kesehatan maternal oleh masyarakat miskin di pedesaan dalam rangka kehamilan aman - Ristrini Wasis Budiarto (Berita Kedokteran Masyarakat (BKM), 2005)
Backgrounds and Methods: The objective of this study is to examine the utilization of maternal health services by poor community in the village in order to make pregnancy safer. This study is 'descriptive-explorative', located in by East Java and Nusa Tenggara Timur (NTT) Provinces. The sample are selected purposively; there are Kupang Regency and 'Timor Tengah Selatan (TTS) and Ponorogo Regency. Two poor sub districts are selected from each regency and from each sub district ten or less poor villages are selected so the sample consists of 55 villages. Mothers are chosen from all child births for six months period. Data collection is conducted by interviewing with postnatal, and unit of analysis is persons/mother. The analysis is conducted descriptively Results and Conclusions: The results of this study show that the first pregnancy examination is 2,7-3,5 months that usually done by village midwife in polindes, posyandu or in the midwife's house. The deliveries is conducted by village midwife (77,8%), in the house of pregnant woman (78,4%). The average of childbirth fee is Rp152.000,00 but there are about 47.3% free. Most postnatal care conducted in polindes (41,8%) and posyandu (33,4%) with average fee Rp7.000,00 and there are also free as it guarantee by PKPS BBM Sector of Health. Keywords: maternal health, village delivery post, making pregnancy safer